Kombucha Beverages Produced from Fruits, Vegetables, and Plants: A Review on Their Pharmacological Activities and Health Benefits - Natthinee Anantachoke; Ratchanee Duangrat; Tanyarat Sutthiphatkul; Duangjai Ochaikul; Supachoke Mangmool (My University, 2023)
Kombucha is a traditional health beverage produced by fermenting sweetened tea with a symbiotic culture of bacteria and yeasts. Consumption of kombucha beverages has been growing and there is kombucha commercially available worldwide as one of the most famous low-alcohol beverages. Kombucha beverages have been claimed to have beneficial effects on human health because they contain a variety of bioactive compounds that possess various functional properties. At present, several kinds of raw material (e.g., milk, fruit, vegetables, and herbs) have been fermented with kombucha consortium and consumed as kombucha beverages. Although several studies have been written regarding the biological activities of kombucha and raw materials, there is however little information available on the characterization of their components as well as the biological activities of fermented kombucha from many raw material mixtures. Several pharmacological activities were reviewed in the scientific literature, describing their potential implications for human health. In addition, the adverse effects and toxicity of kombucha consumption were also reviewed. In this study, we focused on the main and latest studies of the pharmacological effects of kombucha beverages produced from various kinds of raw materials, including antioxidant, anti-inflammatory, immunomodulatory, antimicrobial, anticancer, antidiabetic, antihypertensive, and antihyperlipidemic effects in in vitro and in vivo studies.
Keywords: Health Benefits; Tea Polyphenols and Effects